2016
DOI: 10.7322/jhgd.119302
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference as screening measure for identifying adolescents with overweight and obesity

Abstract: this disease which is low cost, simple and reliable for the assessment of adolescents, especially in primary care. There are numerous anthropometric methods used to evaluate overweight and obesity. Some techniques are applicable for primary health care, like weight and height measurement, waist and hip circumference and the calculation in between these measurements; however, there is still controversy about the effectiveness of some methods for measuring overweight/obesity in children and adolescents 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The PI is the ratio of mass in grams per length in centimeter 3 and not of mass in kilograms per length in meters [3], like TMI. Although the PI was proposed many years ago, according to various authors, the literature about use of PI or TMI in the first years of life is restricted [9,10,21,22,23,24,25,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The PI is the ratio of mass in grams per length in centimeter 3 and not of mass in kilograms per length in meters [3], like TMI. Although the PI was proposed many years ago, according to various authors, the literature about use of PI or TMI in the first years of life is restricted [9,10,21,22,23,24,25,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is time consuming to measure weight, height, and interpret the value with a reference chart [7,8]. An important approach to promote early identification and surveillance of overweight and obesity among adolescents is developing an easy to use, inexpensive and reliable screening tool for identifying adolescents with overweight and obesity [9].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, results for AUC values between 70% and 90% in various age-groups were similar to those found in the Iranian cross-sectional study ( 36 ), suggesting that NC could serve to accurately identify children who are overweight or obese. Another Brazilian study, Souza et al ( 39 ), has also established NC as an adequate indicator to identify adolescents with high BMI. Similar to two recent studies ( 40 , 41 ), our results also suggest that NC has good diagnostic ability, as indicated by an AUC >0.65, for identifying overweight and obesity in children and adolescents and could be used to screen for excess body weight in routine medical practice.…”
Section: Discussionmentioning
confidence: 99%